Implementing higher oxygen saturation targets reduced the impact of poor weight gain as a predictor for retinopathy of prematurity. (20th September 2017) - Lundgren, Pia; Hård, Anna–Lena; Wilde, Åsa; Löfqvist, Chatarina; Smith, Lois E. H.; Hellström, Ann
ABSTRACT: Aim: This study evaluated poor weight gain as a risk factor for infants who required treatment for retinopathy of prematurity (ROP), by comparing those born before and after the implementation of higher oxygen saturation (SpO2 ) targets at the Queen Silvia Children's Hospital, Gothenburg, Sweden. Methods: We compared infants born at less than 31 weeks, who were screened and, or, treated for ROP: 127 in 2011–2012 when SpO2 targets were 88–92% and 142 in 2015–2016 when they were 91–95%. The subjects were reviewed for birth characteristics, weekly weight and ROP treatment. Data were analysed using the weight, insulin‐like growth factor 1, neonatal, ROP (WINROP) prediction tool. Results: The 2011–2012 infants who needed ROP treatment (12.6%) had significantly poorer postnatal weight gain than those who did not, but this was not seen in the treated (17.6%) and nontreated ROP groups in 2015–2016. WINROP sensitivity decreased from 87.5% in 2011–12 to 48% in 2015–2016. Conclusion: After the SpO2 target range was increased from 88–92% to 91–95%, postnatal weight gain was no longer a significant risk factor and WINROP lost its ability to predict ROP requiring treatment. Risk factors clearly change as neonatal care develops. Abstract :